Polymyositis Associated with Brainstem Signs in a Dog - Chimenes, Natielly Dias; Caramalac, Silvana Marques; Madrid, Marisol Mara; Palumbo, Mariana Isa Poci; Babo-Terra, Veronica Jorge (Acta Scientiae Veterinariae, 2022)
Background: Polymyositis is a generalized inflammatory myopathy which can lead to rhabdomyolysis. This affection may have several origins, including degenerative, metabolic, autoimmune, or infectious inflammation, ischemic, traumatic, by drug use, induced by toxins and also of idiopathic origin. Diagnosis is made with seric dosage, electrodiagnostic tests and muscle biopsy. Lesions in the rostral oblong medulla may affect the central vestibular system, and there may be signs such as opisthotonos, nystagmus, and strabismus. The aim of this report is to describe a case of a mixed breed dog with manifestation of polymyositis associated with brainstem signs of probable idiopathic origin. Case: A 5-year-old mixed breed male dog was attended with opisthotonos episodes for 2 days, and pelvic limbs extension and thoracic limbs flexion that lasted 10 to 20 min at intervals of approximately 1 h. The animal was anorexic and had also presented one episode of emesis. Upon neurological examination, ventromedial strabismus and Horner’s syndrome was observed on the right side, besides vertical nystagmus, flaccid tetraparesis and absence of proprioception in the four limbs. Biochemical analyses revealed creatine kinase (CK) increased (2,433,9 UI/L - reference: 1.5-28.4 UI/L), and urinalysis showed presence of occult blood without erythrocyturia and dark colored urine. Electrocardiogram (ECG) showed QS wave and deviation of the electrical axis. Treatment with prednisolone (1 mg/kg, BID), phenobarbital (2 mg/kg, BID), maropitant citrate (1 mg/kg in 2 doses), and crystalloid fluid therapy (50 mL/kg/day) were prescribed. On the 4th day, the dog was more active and feeding without a tube, so it recommended keep the treatment at home. On the 10th day, the animal had proprioception present on the 4 limbs and normorexia. Biochemical analyses and urinalysis showed no alterations, but normochromic normochromic anemia with thrombocytopenia and leukocytosis by neutrophilia showed in blood count exam. PCR to Ehrlichia canis, Hepatozoon sp., and Babesia canis resulted negative. On the 15th day, blood count, biochemical analyses and urinalysis showed no alterations. Neurological examination revealed only positional vertical nystagmus. which remained as a sequel. Discussion: Polymyositis may be accompanied by rhabdomyolysis, characterized by acute muscle necrosis, increased CK and myoglobinuria. The animal had polymyositis of acute onset, with myoglobinuria and elevated CK values, whose presentation included myalgia and muscle weakness. In humans, polymyositis is accompanied by changes in electrocardiographic tracing without clinical alterations. In dogs, the first report that showed cardiac involvement was compatible with myocarditis. The changes in ECG in the present case was attributed to failure in myocardial electrical conduction. The patient also showed signs of brainstem and central vestibular system injuries. Stress myopathy, intoxication, snakebite, infectious and metabolic diseases were discarded leading to a clinical suspicion as idiopathic origin. Similar to a published case, the patient of this report received symptomatic and supportive treatment, being discharged from the hospital 20 days after the onset of clinical signs. Thus, polymyositis may be accompanied by signs indicative of brainstem injury. Patients with rhabdomyolysis require intense monitoring due to the high risk of developing acute renal failure. Since no causative agent was identified, symptomatic treatment combined with the prevention of possible complications were fundamental for the maintenance of the animal's life. Keywords: myoglobinuria, rhabdomyolysis, Horner’s syndrome.